Efficacy of ultrasound-guided lumbar plexus block in reducing emergence agitation in children undergoing hip surgery - Wang, Xiaofeng; Chen, Yonglin; Yan, Hai; Chen, Yongzhu; Yang, Yonggang; Xing, Ruyi; Zhang, Yu; Xu, Tao; Zhang, Hui (Frontiers in Medicine, 2025)
ObjectiveEmergence agitation (EA) is a common and challenging postoperative problem in children. We aim to investigate the effect of ultrasound-guided lumbar plexus block on emergence agitation in children undergoing hip surgery.MethodsThis prospective, randomized, controlled study was conducted in children aged 1–6 year undergoing elective hip surgery. Subjects were randomly assigned to receive either ultrasound-guided lumbar plexus block combined with general anesthesia (Group Block, n = 172) or routine general anesthesia (Group Control, n = 172). The primary outcome was the incidence of EA at 30 min after emergence from general anesthesia, assessed using the Pediatric Anesthesia Emergence Delirium (PAED) scale. The secondary outcomes included the incidence of severe EA, postoperative pain evaluated by the Children’s Hospital of Eastern Ontario Pain Scale (CHEOPS) and the incidence of postoperative adverse complications.ResultsThe incidence of EA was significantly lower in Group Block than in Group Control (13.4% vs. 44.2%, p < 0.001). Group Block had a lower incidence of severe EA than Group Control (3.5% vs. 19.1%, p < 0.001). CHEOPS was lower in Group Block than in Group Control [mean (95%CI), 4.4(4.3–4.5) vs.4.9 (4.8–5.0), p < 0.001].ConclusionUltrasound-guided lumbar plexus block could effectively decrease the incidence and severity of emergence agitation in children undergoing hip surgery.